Acute Responses to Forearm Compression of Blood Lactate Accumulation, Heart Rate, Perceived Exertion, and Muscle Pain in Elite Climbers - Engel, Florian Azad; Sperlich, Billy; Stöcker, Urs; Wolf, Peter; Schöffl, Volker; Donath, Lars (Frontiers in Physiology, 2018)
Objectives: To evaluate the immediate responses to forearm compression of blood lactate concentration, heart rate, perceived exertion and local forearm muscle pain during severe climbing in elite climbers. Method: Seven elite climbers (18 ± 2 years; 164 ± 5 cm; 57.8 ± 5.3 kg) performed 3 × 3 climbing bouts with maximal intensity on a distinct 8 m boulder wall (lead grade: 7a–8b) in a single blinded, placebo-controlled cross-over design, wearing either forearm sleeves with compression (verum-compression) or placebo forearm sleeves with no compression (falsum-compression). Each climber’s heart rate was recorded during and capillary blood lactate concentration, perceived exertion and forearm muscle pain were assessed directly after climbing. Result: Heart rate (p = 0.45, ηp2 = 0.12), blood lactate concentrations (p = 0.44, ηp2 = 0.10), perceived exertion levels (p = 0.51, ηp2 = 0.08) and pain perception (p = 0.67, ηp2 = 0.03) were not affected by forearm compression. No condition × time interaction effect (compression × time) occurred for heart rate (p = 0.66, ηp2 = 0.04), blood lactate concentration (p = 0.70, ηp2 = 0.02), perceived exertion (p = 0.20, ηp2 = 0.26) and pain perception (p = 0.62, ηp2 = 0.04). Conclusion: In elite climbers performing severe climbing bouts, sleeves with forearm compression do not alter blood lactate concentration, heart rate, perceived exertion and local forearm muscle pain.